Etiological Profile of Hereditary Hemolytic Anemia among Patients Presenting in Tertiary Care Hospital of Lahore - Nida Rizwan, Shizra Kaleemi, Sadaf Kareem, Sidra Sonia Chaudary, Saad Zafar, Sehr Syed (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Hereditary hemolytic anemia is a frequent genetic condition that can have varied levels of morbidity and death. These genetic diseases raise the burden on the patient as well as society and pose a serious threat to public health. Aim: To determine the frequency of various causes of hereditary hemolytic anemia among patients in a tertiary care hospital. Methodology: It was a descriptive cross sectional study. Patients (n=252) were enrolled through probability convenient sampling. The study was conducted at Pathology Laboratory, Jinnah Hospital, Lahore. Blood samples were taken from all patients for complete blood count, peripheral smear, reticulocyte count, indirect bilirubin, serum lactate dehydrogenase, and direct antiglobulin test. Median corpuscular fragility (MCF) >4.45g/l NaCl was considered positive. Quantitative enzyme-based assays of Glucose 6 phosphate dehydrogenase were determined spectrophotometrically by using Pointe scientific G6PD reagent. Data were entered and analyzed using SPSS v25.0. A p-value of 0.05 was used to define statistical significance after post-stratification analysis using the chi-square test. Results: age range in this study was from 1 to 60 years with a mean age of 29.3±9.5 years. According to causes of heredity hemolytic anemia distribution, Thalassaemia major 137(54.4%) was the most common cause followed by Thalassaemia intermedia at 41(16.3%), Sickle Cell Anemia at 34(13.5%), Heredity spherocytosis as 31(12.3%) and Glucose-6 phosphatase deficiency as 9(3.6%). Practical Implication: As there is a high incidence of anemia among our population and there is lack of local data that specifically addresses this health issue thus current study was planned. This study highlighted that educating the entire medical community could help lower the prevalence of thalassemia major and emphasise the need of diagnosing the thalassemia trait and provide premarital and prenatal counselling. Conclusion: It was concluded that majority of hereditary hemolytic anaemias were hemoglobinopathies, which place a heavy strain on families and society. The occurrence of these conditions can be reduced in large part by prevention. Keywords: Heredity Hemolytic Anemia, Heredity Spherocytosis, Thalassaemia Trait and Prention.